Development and Implementation of a Web-Based IT Boot Camp Application as Community Programming Training Platform - Faza Shafa Azizah; Rita Dewi Risanty; Muhaemin Muhaemin; Megawati Megawati; Alika Raisya (SWAGATI : Journal of Community Service, 2026)
The rapid development of digital technology has encouraged training institutions to adopt information systems that improve the effectiveness of learning management and participant monitoring. IT Training Center is one of the institutions providing programming bootcamp programs to enhance community competencies in information technology. However, the training process still encountered several challenges, including fragmented participant data management across multiple platforms, difficulties in monitoring learning progress, and the absence of an integrated system for evaluating participant performance. Therefore, this community service program aimed to optimize the implementation of programming bootcamps through the implementation and mentoring of the IT-Bootcamp web-based application. The program employed a participatory approach involving the partner throughout the stages of problem identification, needs analysis, application development, system implementation, socialization, mentoring, evaluation, and reporting. The activities involved administrators, mentors, and bootcamp participants at IT Training Center. Program evaluation was conducted through functional testing, direct observation, and a five-point Likert-scale questionnaire distributed to 20 respondents consisting of four administrators, four mentors, and twelve participants. The evaluation results indicated that all assessment indicators achieved the Very Good category, with average scores ranging from 4.38 to 4.92. Users perceived the application as easy to use, effective in supporting participant management, learning material organization, progress monitoring, and learning evaluation. Furthermore, participants reported that the application facilitated access to learning resources and improved the overall learning experience. These findings demonstrate that implementing the IT-Bootcamp application, accompanied by socialization and mentoring activities, successfully strengthened the partner's capacity to manage programming bootcamps more efficiently, systematically, and sustainably.